INTERNAL FORM KEY NOMINATION IN THE INTEGRATION OF THE CONTENT OF MARKA CHEREMSHYNY'S NOVEL "PYSANKY" - Golianych, Maria (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
This article examines the meaning and functional significance of intraform nominations with a pronounced internal form within Marko Cheremshyna's novel "Pysanky." These nominations serve as both a setting and a means of integrating the novel's content. The research proved that among various linguistic means that contribute to the coherence of the text and the development of its evaluative and symbolic meaning, your role belongs to a new word. The significance of such a linguistic unit in an artistic text is significantly enhanced if the internal form of the word is a component of its semantic structure - a conceptual feature fixed in it. The internal form, included in the utterance (through the key nomination), proves how the speaker feels about what he is talking about and shows the communicator's intentions. The article proves: that the key intra-form nomination of the Easter egg in Mark Cheremshina's novel of the same name is a significant semantic scrap of the test, its evaluative and cognitive marker, an expression of hidden signs of its existence. The selected nomination is significant because, in the studied text, this nationally marked linguistic unit acquires additional semantic increments, giving the text integrity and completeness.